Pavement assessment using on-board sound intensity system - Zofka, Adam; Maliszewski, Maciej; Zofka, Ewa; Mechowski, Tomasz (International Conference “Environmental Engineering”, 2017)
The purpose of this paper is to present an innovative method of measuring sound intensity called On-Board Sound Intensity on electric (EV) or hybrid electric vehicle (OBSIe). Typical sources of noise emitted by modern vehicles in urban areas are propulsion noise and noise generated at the tyre/pavement interface. Thinking of a future we can imagine cities full of silent, zero-emission cars. Propulsion noise becomes insignificant while tyre/pavement contact noise can still dominate in the urban, low-speed areas. Current methods of pavement noise measurements are not suited for the application in such scenarios and only partially eliminate the propulsion noise. Thus there is a need for research methods that can assess tyre/pavement noise at speeds lower than 50 km/h which is a threshold between propulsion noise and tyre/pavement noise. Our method de veloped at Road and Bridge Research Institute (IBDiM) in Poland is especially well suited to measure noise intensity in densely populated urban areas where vehicle transport generated noise is problematic. High manoeuvrability of a testing vehicle, quick installation and low cost are only some of the benefits of the OBSIe. An application of the OBSIe method to support sustainable development in the urban areas will be investigated in this paper.